Stable integration of mgfp5 transgenes following Agrobacterium-mediated transformation in Boesenbergia rotunda cell suspension culture - Wong, S.M.; Zoolkefli, F.I.R.M.; Karim, R.; Tan, B.C.; Harikrishna, J.A.; Khalid, N. (Taylor & Francis, 2015)
Boesenbergia rotunda, a herb in the ginger family, contains numerous beneficial compounds, such as flavonoids, flavones and cyclohexenyl chalcone derivatives, that have great potential for pharmaceutical applications. However, the low concentration of the bioactive compounds limits their commercial application. In this study, a simple and reliable Agrobacterium-mediated transformation protocol for B. rotunda cell suspension culture was successfully developed. The minimal inhibitory concentration and natural tolerance of the selective agent, hygromycin, against the cells were 20 mg l−l and 30 mg l−l in liquid media and solid media, respectively. The highest number of transformed regenerants (18 ± 0.00 per ml settled cell volume) was recorded when cells were infected with Agrobacterium tumefaciens harbouring pCAMBIA1304 for 10 min and co-cultivated for 2 days. Prolonged infection time (> 10 min) and co-cultivation period (> 2 days), however, did not increase the transformation efficiencies. The results clearly show that infection and co-cultivation periods strongly influenced the transformation efficiency in ginger. The transformed cells were recovered and showed green fluorescent signals under ultraviolet excitation. An intense blue colour was observed in the transformed cells after β-glucuronidase (GUS) histochemical staining, further confirming the functionality of the GUS enzymes in the regenerants. Polymerase chain reaction analysis of 3-, 6-, 9- and 12-month-old transformed cells confirmed that the protocol enabled stable integration of the mgfp5 gene. Moreover, the comparatively high number of transformed regenerants in this study made it possible to generate a large number of transgenic cells in a short period, which would be useful for high-throughput functional screening of enzymes involved in the biosynthetic pathways of bioactive compounds.